Upaya Meningkatkan Hasil Belajar Fisika Dengan Menerapkan Model Pembelajaran Make A Match - Edy Satianto (JURNAL GLOBAL EDUKASI, 2021)
Abstrak: Classroom Action Research was carried out for two cycles. The subjects in this study were students of class XII IPA 1 SMA Negeri 5 Medan with 26 students. In the first cycle of meeting I, it was found that there were no students who had very good learning motivation, three students who were classified as good, 17 students who were classified as sufficient, and six students who were classified as lacking. In the first cycle of meeting II, it was obtained data that there were no students who obtained very good criteria, ten students were classified as good, 16 students were classified as sufficient, and no students were classified as poor. In the second cycle of meeting I, it was obtained data that two students were classified as very good, 19 students were classified as good, five students were classified as sufficient, and no student was classified as lacking. In the second cycle of the second meeting, it was found that four students were classified as very good, 20 people were classified as good, two people were classified as sufficient, and no student was classified as lacking. The implementation of the action in the second cycle of the second meeting was already getting better results reaching the expected criteria. Students' average value evidences this in the second cycle of the second meeting, which is 79.2. Kata kunci: make a match; wave Abstrak: Penelitian Tindakan Kelas dilaksanakan selama dua siklus. Subjek dalam penelitian ini adalah siswa kelas XII IPA 1 SMA Negeri 5 Medan dengan jumlah siswa 26 orang. Pada siklus I pertemuan I diperoleh data tidak ada siswa yang mempunyai motivasi belajar sangat baik, 3 orang siswa yang tergolong baik, 17 orang siswa yang tergolong cukup, dan 6 orang siswa yang tergolong kurang. Pada siklus I pertemuan II diperoleh data bahwa tidak ada siswa yang memperoleh kriteria sangat baik, 10 orang siswa yang tergolong baik, 16 orang siswa yang tergolong cukup, dan tidak ada siswa yang tergolong kurang. Pada siklus II pertemuan I diperoleh data bahwa 2 orang siswa yang tergolong sangat baik, 19 orang siswa tergolong baik, 5 orang siswa tergolong cukup dan tidak ada siswa yang tergolong kurang. Pada siklus II pertemuan II diperoleh data bahwa 4 orang siswa tergolong sangat baik, 20 orang tergolong baik, 2 orang tergolong cukup, dan tidak ada siswa yang tergolong kurang. Pada pelaksanaan tindakan pada siklus II pertemuan II sudah mendapatkan hasil yang lebih baik mencapai kriteria yang diharapkan. Hal ini di buktikan dari nilai rata-rata yang diperoleh siswa pada siklus II pertemuan ke II, yaitu 79,2. Kata kunci: gelombang; make a match